2019
DOI: 10.1002/ece3.5135
|View full text |Cite
|
Sign up to set email alerts
|

Changes in genetic diversity and differentiation in Red‐cockaded woodpeckers (Dryobates borealis) over the past century

Abstract: Red‐cockaded woodpeckers (RCW; Dryobates borealis ) declined after human activities reduced their fire‐maintained pine ecosystem to <3% of its historical range in the southeastern United States and degraded remaining habitat. An estimated 1.6 million RCW cooperative breeding groups declined to about 3,500 groups with no more than 10,000 birds by 1978. Management has increased RCW population abundances since they were at their lowest in the 1990s. However, no range‐wide study has been und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…RCW populations continued to decline through the 1980s, but increased to more than 5500 group territories and >14 000 birds by the early 2000s (USFWS 2003). Populations across the species' range have remained stable or continued to increase, with range-wide population size recently estimated at more than 7800 group territories (Miller et al 2019). As a social species, increases in group density that contribute to population recovery result in increasing group size trends over the long-term due to improved demographic connectivity Mikusinski 1998, Schiegg et al 2006).…”
mentioning
confidence: 99%
“…RCW populations continued to decline through the 1980s, but increased to more than 5500 group territories and >14 000 birds by the early 2000s (USFWS 2003). Populations across the species' range have remained stable or continued to increase, with range-wide population size recently estimated at more than 7800 group territories (Miller et al 2019). As a social species, increases in group density that contribute to population recovery result in increasing group size trends over the long-term due to improved demographic connectivity Mikusinski 1998, Schiegg et al 2006).…”
mentioning
confidence: 99%
“…Other studies found a decreasing genetic diversity and increasing genetic differentiation, e.g. in plants (Finger et al, 2012), mammals (Miller & Waits, 2003), birds (Miller et al, 2019), and insects (Gauthier et al, 2020;Harper et al, 2006;Nakahama & Isagi, 2018). Most of the above-mentioned studies investigated relatively long time periods of 25 years or longer (e.g.…”
Section: Introductionmentioning
confidence: 99%